1980
DOI: 10.1104/pp.66.5.1001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Subcellular Localization of Phospholipase D and Phosphatidic Acid Phosphatase in Mung Bean Cotyledons

Abstract: Mixed micelles of 32P-labeled phosphatidylcholine or phosphatidic acid (PA) and the nonionic detergent octylphenol polyethylene oxide were used to assay the activities of phospholipase D and PA phosphatase in crude extracts of mung bean ( Vigna radiata) cotyledons. Together these enzymes degrade phosphatidylcholine to free choline, inorganic phosphate, and sn-1,2-diacylglycerol. Here, we extend a preliminary observation (9) showing that extracts of mung bean cotyledons rapidly degrade PC and PE. The two enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…It is worth noting in this context that protein bodies are part of the vacuolar/lysosomal compartment of plant cells. Recent evidence shows that protein bodies are derived from vacuoles during seed maturation (5,6,27) and that they contain numerous acid hydrolases (14,17,20,26). Protein bodies therefore have an enzymic complement and function similar to that of the central vacuole of plant cells or the lysosomes of animal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting in this context that protein bodies are part of the vacuolar/lysosomal compartment of plant cells. Recent evidence shows that protein bodies are derived from vacuoles during seed maturation (5,6,27) and that they contain numerous acid hydrolases (14,17,20,26). Protein bodies therefore have an enzymic complement and function similar to that of the central vacuole of plant cells or the lysosomes of animal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reserve protein polypeptides were isolated with IgG-PBE-Sepharose, fractionated by SDS PAGE, and a fluorograph was prepared . (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), whereas the synthesis of the larger vicilin polypeptides (Mr 75,000 and 70,000) was most pronounced at the end of the developmental period .…”
Section: Newly Synthesized Polypeptides In the Ermentioning
confidence: 99%
“…Widespread evidence for the concerted action of PLD and PAP includes reports in mammalian literature that demonstrate DAG production from endothelialderived PC (Martin, 1988) and endogenous DAG generation in human polymorphonuclear leukocytes where DAG stimulated 5-lipoxygenase enzyme activity and function (Albert et al, 2008). In plants, isolated protein bodies from seedlings show both activities of PLD and PAP (Herman and Chrispeels, 1980), and studies of AtPLD z1 and AtPLD z2 suggest the supply of DAG for galactolipid synthesis is dependent on this pathway and also subverts phosphorus starvation (Cruz-Ramírez et al, 2006;Li et al, 2006). It has been shown that knock-down of PLDa in soybean leads to reduced PUFAs in TAG (Lee et al, 2011), implicating a flux from PC to TAG through PLD-PAP without a requirement for PDCT involvement.…”
Section: Carbon Flux Between Dag and Pc Are Highly Interconnected In mentioning
confidence: 99%
“…In plants PLD is known to be involved in several cellular processes but its role has not been established clearly. The enzyme is present in the protein bodies of germinating mung bean cotyledons [5] and is associated with plasma and intracellular membranes in seedling tissues of castor bean [6]. Activity changes have been observed in conjunction with water stress [7], senescence [S] and pathogenic infection [9].…”
mentioning
confidence: 99%